Amino-Acid Sequence of Rabbit Skeletal Tropomyosin and Its Coiled-Coil Structure - Sodek, J. (1972)
A tentative amino-acid sequence for the COOH-terminal half of rabbit skeletal tropomyosin is reported. These studies confirm our previous conclusions that this tropomyosin consists of several different but similar polypeptide chains. In the sequence, nonpolar residues occur in two series at intervals of seven residues. Amino-acid residues in series I are three residues on the NH(2)-terminal side of, and four residues on the COOH-terminal side of, residues in series II. The presence of occasional charged or ambivalent residues in the positions of series I or II does not lead to a disruption of this long-range pattern. The majority of residues located between the nonpolar residues are charged or polar amino acids. Two highly similar or identical α-helices with the reported sequence can be packed together in parallel in a coiled-coil structure. These may be in register or staggered by seven residues or some multiple of it. The observation that groups of small hydrophobic side chains appear to alternate with groups of bulky side chains suggests that a staggered arrangement of the two α-helices would maximize the regularity and hydrophobic interactions of the coiled-coil. Model building considerations show that this would occur with a stagger of 14 residues. Such an arrangement could account for the end-to-end aggregation of tropomyosin in solution, and in crystal and tactoid filaments. However, a structure in which the two polypeptides are in register cannot be ruled out.